Canine and feline lungworm infections in the UK. Issue 7 (13th July 2017) - Helm, Jenny; Morgan, Eric
Abstract : Lungworm infections in dogs and cats have gained attention in practice in recent years, driven largely by the spread of Angiostrongylus vasorum outside historically recognised endemic foci and associated efforts to increase awareness and encourage treatment and prevention. While several species of lungworm are clinically relevant, A vasorum in particular is common and can be highly pathogenic in dogs in the UK. The tools available for the diagnosis and treatment of lungworm infections have advanced and informed clinicians are well equipped to deal with threats from this group of parasites. This article reviews the helminth parasites of the canine and feline respiratory systems, and summarises their life cycles, epidemiology, pathogenesis, diagnosis, treatment and prevention. It also discusses apparent changes in the epidemiological patterns of lungworm infections in both species and the implications for risk assessment and management.